Neuroprotective Actions of Neurosteroids - Borowicz, Kinga; Czuczwar, Stanislaw; Piskorska, Barbara; Banach, Monika (Frontiers in Endocrinology, 2011)
Neurosteroids were initially defined as steroid hormones locally synthesized within the nervous tissue. Subsequently, they were described as steroid hormone derivatives that devoid hormonal action but still affect neuronal excitability through modulation of ionotropic receptors. Neurosteroids are further subdivided into natural (produced in the brain) and synthetic. Both hormones and their derivatives share, however, most of the physiological functions. It is usually very difficult to distinguish the effects of hormones and their metabolites. All these substances may influence seizure phenomena and exhibit neuroprotective effects. Neuroprotection offered by steroid hormones may be realized in both genomic and nongenomic mechanisms and involve regulation of the pro- and antiapoptotic factors expression, intracellular signaling pathways, neurotransmission, oxidative and inflammatory processes. Since regular neurosteroids show no affinity for steroid receptors, they may act only in a nongenomic mode. Multiple studies have been conducted so far to show efficacy of neurosteroids in the treatment of the central and peripheral nervous system injury, ischemia, neurodegenerative diseases or seizures. In this review we focused primarily on neurosteroid mechanisms of action and their role in the process of neurodegeneration. Most of the data refers to results obtained in experimental studies. However, it should be realized that knowledge about neuroactive steroids remains still incomplete and requires confirmation in clinical conditions.